Pentachlorophenol removal by Pleurotus pulmonarius in submerged cultures - Souza,Daniela Farani de (2011)
Pentachlorophenol (PCP) removal by Pleurotus pulmonarius grown in submerged cultures in the presence and absence of laccase inducers was studied in this work. When PCP was added to a final concentration of 25 mg·L-1 in submerged cultures actively producing laccase, 70% of the PCP was removed after 96 h. The removal of PCP was less than 20% in the cultures with low laccase activity. The results suggested that laccase played an important role in the biodegradation of PCP by P. pulmonarius and that for bioremediation purposes the fungus must be cultured under the conditions of active laccase production.